Economics of population versus economic demography - A. A. Tkachenko (Статистика и экономика, 2017)
The article specifies the correlation between economic demography and the economy of population as the most important scientific areas of modern research. It is concluded that the Russian scientific community lags in the development of these sciences from the world scientific thought. Special attention is paid to the works and ideas of S. Kuznets and Amartya Sen as outstanding researchers of the interrelationships between the population and the economy. It is emphasized that their contribution was not only theoretical but also of practical importance. The importance of G. Myrdal’s works for modern studies of the consequences of population aging is considered. The article examines foreign training courses on “Population Economics”, presented at the Universities of Wisconsin and McMaster, their analysis led to the conclusion that the preparation of textbooks on courses is less productive than the use of scientific articles in journals, containing more recent ideas and achievements of science. The author considers the system, proposed in the course Michel Grignon and Byron G. Spencer «The Economics of Population» more preferable. The article substantiates the opinion that the economic theory of well-being should be the core of the population economy. It is concluded that the differences between economic demography and the economy of population are not just differences between the micro- and macro levels, as some authors write, but the transition to large scales and entropy.The author identifies three most important areas of demo-economic research, which include research in the field of human capital, international economic migration, especially remittance, analysis of the stratification of the population and society by the income in the global and national economies. One can single out the general area of interests of the population economy and economic demography in which these sciences are almost impossible to divide and in which only their joint research is effective: the economy of aging and the economy of generations.